Introduction - Magowan, Fiona (The Australian journal of anthropology, 2001)
Syncretism has a long and fractured history within the anthropological study of religions. This edition of TAJA offers readers a critical reanalysis of the enduring anthropological enchantment with syncretism as contributors reassess the value of this theoretical concept in their own work in Melanesia, Aboriginal Australia, Malaysia, Indonesia and India. The authors examine a range of cultural contexts in which syncretism occurs and outline the theoretical possibilities and limitations when the concept is recast and taken beyond existing paradigms. In this broadened sense, syncretism may today be viewed as an indication of indigenous creativity, agency and autonomy, a view far removed from its earlier association with cultural inauthenticity, pollution and even debasement.